Influence of Business Relation and Innovative Organization on Competitive Advantage with Service Quality as Mediator of Small and Medium Sized Construction Contracting Businesses for Industrial Plant Construction - Wongkamlue, Supot (Sripatum Review of Humanities and Social Sciences, 2024)
The purpose of this research was to find a model of competitive advantage and to analyze the influence of service quality, organizational innovation and business relationships that result in a competitive advantage for SMEs for industrial factory construction. It used a mixed method research. The qualitative research conducted interviews with a group of 21 small and medium sized construction contractors with expertise in industrial factory construction to bring information to summarize the important points in the questionnaire questions. The quantitative research used questionnaires as a tool to collect data from a sample group of 364 small and medium sized construction contractors with expertise in industrial factory construction. Data was analyzed using structural equation modeling analysis. The results of the study found that business relationship, organizational innovation has a direct influence and indirectly through service quality to the competitive advantage of the construction industry. Service quality has a direct influence on the competitive advantage of the construction contracting industry which is a small and medium sized enterprise.